Family Therapy in Improving the Psychological Dynamics of Fishermen's Families in Kampung Bahari Nusantara - Hidayah, Lien Ramadhani Alfi; Nurmalitasari, Femmi (KnE Social Sciences, 2024)
In the daily lives of fishermen, their livelihoods come from natural resources, namely the sea, which makes them have to adjust to the natural situations and conditions. When natural conditions are uncertain, it can cause the mental or psychological condition of fishermen’s families to decline so that it requires an intervention. The goal is to improve the psychological condition of fishing families, located in Kampung Bahari Nusantara on the South Coast of Malang Regency, by providing guidance through therapy. The therapy carried out is a family therapy to reduce the signs or symptoms that can threaten family welfare in families with problems or disorders. Activities were carried out on July 5 – 7, 2023, to conduct data collection interviews and on October 31, 2023, to carry out the family therapy interventions. The methods used were interviews and observations in collecting data, lectures, and group guidance in conducting family therapy interventions. The results of the therapy carried out have a positive impact on the participants to be more open to other family members, understand the differences in the nature of family members, share anxiety still, and can make the family more harmonious. Keywords: psychological dynamics, family therapy, fisherman